Review of The Disney Princess Phenomenon - Tóth, Zsófia Anna (AMERICANA E-journal of American Studies in Hungary, 2023)
The Disney Princess Phenomenon. A Feminist Analysis Robyn Muir Bristol: Bristol University Press, 2023. 218 p. ISBN 978-1-5292-2209-8 hardcover, ISBN 978-1-5292-2210-4 ePub, ISBN 978-1-5292-2211-1 ePdf